Deconstructing Attributes of Constitutional Legitimacy: A Case Study of Indian Constitution - Negi, Abhishek; Irshad, Mohammed; Luthviati, Resti Dian (Journal of Human Rights, Culture and Legal System, 2024)
This study aims to critically investigate the common perception of constitutional adherence and trace it to the Constitution's legitimacy. However, the existing literature on the subject highlight lacunae in the predominant approaches to legitimacy. Concretizing a theoretical framework to address such lacunas, the authors claim that constitutional legitimacy is a dimensional non-constant and cannot be restricted to one principle or theory. The study adopts a doctrinal research methodology. The study results show that constitutional legitimacy should be understood holistically and not just through the instrumentalities of the 'We the People' paradigm of the Indian Constitution. The representative legitimacy or the idea of 'We the people' is an aspirational ideal; hence, dynamic and aspiration may become a reality as more and more citizens get socialized into the institutions created by constitutional democracy. In this context, the study argues that the legitimacy of the Indian Constitution cannot be put strictly within the brackets of representational legitimacy because it may safely claim legitimacy under reason-based, substantive, negligible, and motivated-consent models.